2000
DOI: 10.1006/jfbi.2000.1397
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution and feeding of larval blue whiting in turbulent waters above Porcupine Bank

Abstract: In April 1995 a patch of blue whiting larvae Micromesistius poutassou was found at low illumination levels below 20 m depth near Porcupine Bank, west of Ireland, together with high densities of copepod nauplii and reduced turbulence rates, suggesting that larval blue whiting vertical distribution was determined by prey concentration, illumination and turbulence. Most (83·8%) larvae (2·0-7·5 mm L s ) had food in their guts. Feeding incidence and feeding intensities increased with increasing larval length. Only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 13 publications
0
16
1
Order By: Relevance
“…Youngest fish larvae are often less aggregated and occur at greater depths than larger fish larvae, particularly under high turbulent energy dissipation rates. With improving swimming ability during growth, larger larvae become more able to compensate for turbulent dispersion and tend to be more aggregated (Heath et al 1988;Heath 1992;Hillgruber and Kloppmann 2000). The results of our study were the opposite of the aforementioned scenario, i.e., mackerel larvae <5.0 mm were highly aggregated near the thermocline and showed distinct diel vertical migration patterns, while mackerel larvae ≥5.0 mm were more dispersed with only slight diurnal movement patterns discernible.…”
Section: Vertical Distribution Of Atlantic Mackerel Larvaecontrasting
confidence: 68%
See 3 more Smart Citations
“…Youngest fish larvae are often less aggregated and occur at greater depths than larger fish larvae, particularly under high turbulent energy dissipation rates. With improving swimming ability during growth, larger larvae become more able to compensate for turbulent dispersion and tend to be more aggregated (Heath et al 1988;Heath 1992;Hillgruber and Kloppmann 2000). The results of our study were the opposite of the aforementioned scenario, i.e., mackerel larvae <5.0 mm were highly aggregated near the thermocline and showed distinct diel vertical migration patterns, while mackerel larvae ≥5.0 mm were more dispersed with only slight diurnal movement patterns discernible.…”
Section: Vertical Distribution Of Atlantic Mackerel Larvaecontrasting
confidence: 68%
“…Fiksen et al (1998) performed a modeling study and observed that both turbulence and light could have a strong impact on larval ingestion rates. While turbulence in the present study was at a level that proved not to be beneficial for larval blue whiting foraging success (Hillgruber and Kloppmann 2000), it did not change over time, so that changes in the composition of the diet should be solely due to light. However, mackerel larvae of both size classes ingested proportionately more smaller prey at lower light levels.…”
Section: Cannibalistic Feeding In Atlantic Mackerel Larvaementioning
confidence: 55%
See 2 more Smart Citations
“…These behaviours are important mechanisms which differ among larval fish species and which nonetheless lead to the dominance of larval diets by a relatively few species (Munk 1995, Hillgruber et al 1997, Heath & Lough 2007. Our modelling approach can potentially enable us to investigate how larval diets in the field change depending on prey characteristics and turbulence conditions (Dower et al 1998, Hillgruber & Kloppmann 2000, Fiksen & MacKenzie 2002. Future climate change will affect not only the spatial and temporal pattern of exposure of larvae to wind and tidally induced turbulence, but will also affect the relative timing of production of individual species of zooplankton (Edwards & Richardson 2004) and larval fish (Greve et al 2005).…”
Section: Future Prospectsmentioning
confidence: 99%